HLA‐DRB and HLA‐DQA/HLA‐DQB allele and haplotype frequencies in Iranian patients with aggressive periodontitis. (14th January 2013) - Mousavi Jazi, M.; Solgi, G.; Asl Roosta, H.; Noshad, S.; Moslemi, N.; Sadrimanesh, R.; Moradi, B.; A. Amirzargar, A.
<x xml:space="preserve">Abstract</x> Background and Objective Genetic backgrounds play a key role in susceptibility to and protection against a spectrum of periodontal diseases. Like other infectious diseases, the human leukocyte antigen (HLA) have been found to be associated with periodontitis. This study aimed to investigate differences in allele and haplotype frequencies of HLA class II antigens in a sample of Iranian patients with aggressive periodontitis compared with a healthy control group. Material and Methods Fifty unrelated patients with aggressive periodontitis and 130 healthy volunteers were enrolled in this study. HLA genotyping for HLA‐DRB, HLA‐DQA1 and HLA‐DQB1 was performed using the PCR with sequence‐specific primers. Allele and haplotype frequencies were compared across groups. Results The frequencies of HLA‐DQA1*03:01, HLA‐DQB1*03:02 and HLA‐DQB1*03:05 alleles, as well as that of the HLA‐DRB1*04:01 allele, were significantly higher in patients with aggressive periodontitis compared with control subjects (p = 0.01, p = 0.04, p = 0.05 and p = 0.04, respectively). In contrast, the frequency of the HLA‐DQB1*0603 allele was significantly lower in patients with aggressive periodontitis compared with control subjects (p = 0.006; odds ratio = 0.20). With regard to haplotype association, a significantly higher frequency of two haplotypes – HLA‐DRB1*04:01/HLA‐DQA1*03:01/HLA‐DQB1*03:02 and HLA‐DRB1*16:01/HLA‐DQA1*01:03/HLA‐DQB1*05:01 – was observed in patients with aggressive periodontitis compared with healthy controls (p = 0.01, odds ratio = 2.56 and p = 0.05, odds ratio = 5.38, respectively). Conclusion These results provide additional evidence that class II HLA polymorphisms, particularly in the DQ locus, are associated with protection against and susceptibility to aggressive periodontitis.